Foreword / Prólogo / Avant Propos - Romagosa I.; Barjol J.L. (Present and future of the Mediterranean olive sector, 2013)
Foreword.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)